2014
DOI: 10.1002/2013jc009688
|View full text |Cite
|
Sign up to set email alerts
|

Meridional volume transport in the South Pacific: Mean and SAM-related variability

Abstract: The large increase in upper-ocean sampling during the past decade enables improved estimation of the mean meridional volume transport in the midlatitude South Pacific, and hence of the climatically important Meridional Overturning Circulation. Transport is computed using Argo float profile data for geostrophic shear and trajectory data for reference velocities at 1000 m. For the period 2004-2012, the mean geostrophic transport across 32 S is 20.6 6 6.0 Sv in the top 2000 m of the ocean. From west to east, this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 41 publications
3
21
0
Order By: Relevance
“…Analysis of the mooring array at 27°S revealed that occasionally the EAC recirculation extended offshore of the mooring array (155.30°E) and was stronger/similar magnitude to that of the poleward EAC transport (Sloyan et al, ). The ozROMS transport estimate of 13 ± 4.9 Sv (Table ) for the EAC recirculation at 32°S was similar (16 ± 3.6 Sv) to that by Zilberman et al (). The EAC recirculation was also present offshore of the EAC extension at 36°S (0–2,000 m) with EAC transport extended from the coast to 152.5°E and the EAC recirculation between ∼152.5°E and 154.5°E (x4; Figure d).…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…Analysis of the mooring array at 27°S revealed that occasionally the EAC recirculation extended offshore of the mooring array (155.30°E) and was stronger/similar magnitude to that of the poleward EAC transport (Sloyan et al, ). The ozROMS transport estimate of 13 ± 4.9 Sv (Table ) for the EAC recirculation at 32°S was similar (16 ± 3.6 Sv) to that by Zilberman et al (). The EAC recirculation was also present offshore of the EAC extension at 36°S (0–2,000 m) with EAC transport extended from the coast to 152.5°E and the EAC recirculation between ∼152.5°E and 154.5°E (x4; Figure d).…”
Section: Resultssupporting
confidence: 83%
“…Cumulative transport across the EAC and EAC extension indicated a reversing flow pattern with both southward and northward circulation with the latter associated with the EAC recirculation (Zilberman et al, ). At 18°S EAC transport extended from the coast to 148°E with the EAC recirculation (northward) between 148°E and 152°E (x2; Figure d).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This vision of the impact of mesoscale turbulence on ocean properties was well confirmed by Ocean Global Circulation Models and climate studies [ Griffies et al ., ]. SSH observations led to estimates of the near‐surface ocean horizontal circulation and, once combined with Argo data, to estimates of the horizontal transport of heat and tracers [ Zilberman et al ., ]. The upcoming launch of a new generation of wide‐swath altimeters (SWOT, 2020) is expected to be the next stride forward: the high resolution (down to 15 km) maps of SSH that will be collected should provide access to the oceanic 3‐D circulation and associated vertical transports of biochemical tracers [ Fu et al ., ].…”
Section: Introductionmentioning
confidence: 99%